Production of hydrogen peroxide and expression of ROS‐generating genes in peach flower petals in response to host and non‐host fungal pathogens. (7th September 2012) - Liu, J.; Macarisin, D.; Wisniewski, M.; Sui, Y.; Droby, S.; Norelli, J.; Hershkovitz, V.
<x xml:space="preserve">Abstract</x> Reactive oxygen species (ROS) play dual roles in plant–microbe interactions in that they can either stimulate host resistance or enhance pathogen virulence. Innate resistance in peach (Prunus persica) to the brown rot fungal pathogen Monilinia fructicola is very limited, and knowledge of the mechanism of virulence is rudimentary. In this study, production of hydrogen peroxide, a major component of ROS, was determined in peach flower petals in response to M. fructicola (a host pathogen) and Penicillium digitatum (a non‐host pathogen). Monilinia fructicola was able to infect flower petals while P. digitatum was not. During the host‐specific interaction, M. fructicola induced hydrogen peroxide accumulation in flower petals. Application of exogenous antioxidants significantly reduced hydrogen peroxide accumulation as well as the incidence of brown rot disease. Application of M. fructicola spores to the surface of intact flower petals induced gene expression and increased enzyme activity of NADPH oxidase and cell wall peroxidase in host tissues, resulting in the production of hydrogen peroxide. Petals inoculated with M. fructicola exhibited high levels of protein carbonylation and lipid peroxidation. No significant response in gene expression, enzyme activity or hydrogen peroxide levels was observed in peach flower petals treated with P. digitatum. These results suggest that M. fructicola, as with other necrotrophic fungi, uses the strong oxidative response as part of a virulence mechanism.